Seanza lectures: Lectures Delivered at the Seventh Seanza Central Banking Course held in Colombo, 3 July - 12 Septeber, 1968 (Ceylon : Central Bank of Ceylon, 1968)
This is a compilation of lectures delivered at Central Bank of Ceylon by the Seanza group in 1968.
osc 12/05/17
Loans
Keywords: Central Banking